2015
DOI: 10.1016/j.cca.2015.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of equations for the calculation of LDL-cholesterol in hospitalized patients

Abstract: Highlights• We evaluated the Friedewald Equation and three other recently developed formulae.• The de Cordova, Chen & Hattori formulae were used in patients with co-morbidities.• More than 14 000 lipid profiles were compared with direct measurement of LDL-C.• The Hattori formula showed the best performance over all lipid values.• Alternative formulae should be implemented in hospitalized patients. Conclusions: We observe favorable correlations of the de Cordova formula withFriedewald at low TG values. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 35 publications
3
26
3
2
Order By: Relevance
“…Martins et al recently reported that the Hattori formula performed the best in hospitalized patients when compared to the Friedewald, Chen and Cordova equations. 27 Although direct LDL-C measurement was used for reference value in comparisons (as in our study), the use of different reagents and instruments for lipid measurements as well as different ethnicities and populations with various health conditions might have caused the discordant findings with our results. On the contrary, Oliveira et al concluded that the Friedewald equation showed the best accuracy when compared to the Chen, Anandaraja, and Vujovic (which was not included in this study) formulas.…”
Section: Discussionmentioning
confidence: 54%
“…Martins et al recently reported that the Hattori formula performed the best in hospitalized patients when compared to the Friedewald, Chen and Cordova equations. 27 Although direct LDL-C measurement was used for reference value in comparisons (as in our study), the use of different reagents and instruments for lipid measurements as well as different ethnicities and populations with various health conditions might have caused the discordant findings with our results. On the contrary, Oliveira et al concluded that the Friedewald equation showed the best accuracy when compared to the Chen, Anandaraja, and Vujovic (which was not included in this study) formulas.…”
Section: Discussionmentioning
confidence: 54%
“…Since Scharnagl et al first reported the underestimation of the Friedewald formula, 12) a number of other studies have described the underestimation and inaccuracy of the Friedewald formula, especially in extreme lipid values and with comorbidities. 7) 8) 12) 13) 14) 15) 16) 17) Most alternative formulas have been developed using multivariate linear regression analysis with LDL-C as a dependent variable and total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and TG as independent variables. 7) 8) 9) 10) 11) 18) Unlike the other formulas, the Anandaraja formula was developed in order to calculate LDL-C without using HDL-C as an independent variable.…”
Section: Introductionmentioning
confidence: 99%
“…Although such various LDL-C formulas have been developed, only a small number of studies have compared them. 13) 14) 15) 16) 17) LDL-C can be measured to identify high-risk individuals in the mass screening, as well as to assess an individual's cardiovascular risk among known high risk patients. 1) 2) 3) 4) 19) However, previous studies have not separately compared the accuracy of calculated LDL-C in both the general population and in high-risk patients of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the profile of serum lipids and (apo)lipoproteins was applied to identify the independent predictors of LDLc and propose the most accurate formula for calculating serum LDLc. Various equations have been derived to calculate serum LDLc by linear regression analysis (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The concentration of LDLc has been measured directly by beta-quantification (5,6,21) or the new homogeneous assay (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The number of these formulae has been increased because the homogenous direct assay of LDLc is easier and more available than beta-quantification. In the more recent method of Martin et al, the coefficient of triglyceride in Friedewald equation is assumed to be adjustable relative to nonHDLc and triglyceride (21,22). The validity of the original Friedewald and the new methods have been questioned in recent studies (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%